PENGARUH PEMBERIAN RUMEN UNDEGRADED PROTEIN TERHADAP PRODUKSI DAN REPRODUKSI SAPI PERAH - ROCHIJAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study was conducted to determine the effect of supplementation high rumen undegraded protein on production and reproduction performance of early lactation dairy cows. This research was located in UPTD BPBPTDK Department of Agriculture Daerah Istimewa Yogyakarta form September 2013 until August 2014. Twelve early lactation Friesian Holstein Crossbred (PFH) cows were divided into two groups. Six animals were used as a control group and another group as treatment objects. The feed is forages and concentrates with a ratio of 60 : 40 in dry matter. The cow feeds after parturition. The control group getting concentrate containing dry matter (DM) 88.24%, crude protein (CP) 18.55%, rumen undegraded protein (RUP) 27.47%, and total digestible nutrien (TDN) 56.94%, while the treatment group getting concentrate containing dry matter (DM) 89.06%, crude protein (CP) 18.83%, rumen undegraded protein (RUP) 32.78%, and total digestible nutrien (TDN) 58.91%. Water was given by ad libitum. The variable measured were feed intake, milk production and composition (fat, protein, lactose, solid non fat and total solid content), milk urea nitrogen (MUN) dan blood urea nitrogen (BUN) value, changes in body weight and body condition score (BCS), response estrous indication and behavior, concentration of profile progesteron hormones, and reproduction performance (post partum mating (PPM), service per conception (S/C) and days open (DO)). The data response estrous indication and behavior obtained were analyzed descriptively and the rest data were tested using T-test analysis. Results showed that dry matter (DM) and organic matter (OM) consumption, crude protein (CP) consumption, crude fiber (CF) consumption, total digestible nutrien (TDN) consumption, milk production, milk fat content and production, milk lactose content and production, SNF content, TS content, changes in body weight and body condition score (BCS), concentration of profile progesteron hormones, PPM, S/C and DO between control and treatment group were not significant. Milk protein content and production, average MUN and BUN value on supplementation high rumen undegraded protein between control and treatment group were significant (P<0.05). The average value of each group is milk protein content 2.57 Â± 0.15 vs. 2.80 Â± 0.15%